Differential Perceptions of Noninvasive Ventilation in Intensive Care among Medical Caregivers, Patients, and Their Relatives: A Multicenter Prospective Study—The PARVENIR Study. (June 2016) - Schmidt, Matthieu; Boutmy-Deslandes, Emmanuelle; Perbet, Sébastien; Mongardon, Nicolas; Dres, Martin; Razazi, Keyvan; Guerot, Emmanuel; Terzi, Nicolas; Andrivet, Pierre; Alves, Mikael; Sonneville, Romain; Cracco, Christophe; et al.
Abstract : Background: Noninvasive ventilation (NIV) requires a close "partnership" between a conscious patient and the patient's caregivers. Specific perceptions of NIV stakeholders and their impact have been poorly described to date. The objectives of this study were to compare the perceptions of NIV by intensive care unit (ICU) physicians, nurses, patients, and their relatives and to explore factors associated with caregivers' willingness to administer NIV and patients' and relatives' anxiety in relation to NIV. Methods: This is a prospective, multicenter questionnaire-based study. Results: Three hundred and eleven ICU physicians, 752 nurses, 396 patients, and 145 relatives from 32 ICUs answered the questionnaire. Nurses generally reported more negative feelings and more frequent regrets about providing NIV (median score, 3; interquartile range, [1 to 5] vs. 1 [1 to 5]; P < 0.0001) compared to ICU physicians. Sixty-four percent of ICU physicians and only 32% of nurses reported a high level of willingness to administer NIV, which was independently associated with NIV case-volume and workload. A high NIV session–related level of anxiety was observed in 37% of patients and 45% of relatives. " Dyspnea during NIV, " "long NIV session, " and "the need to have someone at the bedside" were identified as independent risk factors of high anxiety in patients. Conclusions: Lack of willingness of caregivers to administer NIV and a high level of anxiety of patients and relatives in relation to NIV are frequent in the ICU. Most factors associated with low willingness to administer NIV by nurses or anxiety in patients and relatives may be amenable to change. Interventional studies are now warranted to evaluate how to reduce these risk factors and therefore contribute to better management of a potentially traumatic experience. (Anesthesiology 2016; 124:1347-59) Abstract : A large-sample questionnaire (396 patients, 1, 063 clinicians, and 145 relatives) from 32 intensive care units revealed that concerns about noninvasive ventilation were greatest among nurses (workload) and patients (dyspnea, anxiety). Future research may reveal how to improve the effectiveness and acceptance of noninvasive ventilation.Supplemental Digital Content is available in the text.